Terminological Usage Related to Dyspnea by Nursing Staff: A Cross-Sectional Questionnaire Survey - Yuko Nemoto; Sayuri Suzuki; Shinichiro Okauchi; Katsunori Kagohashi; Hiroaki Satoh (JMIR Publications, 2020)
In recent years, additional expressions such as 'sensation of breathing discomfort' and 'discomfort of dyspnea' are being used in daily nursing care in Japan. To better understand the current status of the use of these terms by nurses, and to ascertain what the term 'dyspnea' may not express, we designed an original questionnaire and conducted a study with all nurses at our hospital. The questionnaire included questions to determine if nurses used these terms, and in what context. Of the 279 nurses in our hospital, 225 (80.6%) responded. Three-quarters of nurses indicated that they use these terms in clinical nursing practice. There was no difference in the usage of these terms between nurses who had or had not worked in a respiratory outpatients/ward. However, the percentage of nurses using these terms was higher amongst those with 10 years or less nursing experience compared with those with more than 10 years' experience. Open-ended questions revealed that these terms were used to communicate information between nurses and between nurses and patients' families. Our observations need to be verified in large-scale studies to determine if these terms are meaningful for nursing practice in that they describe something not expressed with 'dyspnea'. There is the possibility of confusion due to the use of inappropriate terms and a lack of education on the subject. Many nurses used these terms, and there may be things that the term 'dyspnea' could not express. The results of this study can be used to identify something that is lacking in communication about dyspnea between nurses, nurses and patients, and nurses and patients' families.